Effect of environmental context on ICT adoption among rural-based small and medium enterprises in Malaysia - Jaganathan, Mathivannan; Mahmood, Rosli; Ahmad, Shuhymee; Ahmad, Ismail (AENSI Journals, 2014)
The objective of this paper is to examine the effect of the environmental context on the adoption of ICT among rural-based small and medium enterprises (SMEs) in Malaysia.Two hypotheses were formulated to answer the objectives of study; (i) there is significant relationship between information intensity and ICT adoption, and (ii) there is significant relationship between competition intensity and ICT adoption.A quantitative research design based on the questionnaire survey was used to collect the data. A total of 1000 questionnaires were mailed and 167 usable responses were received.The findings reveal that both information intensity and competition intensity had positive significant relationship with ICT adoption among rural-based SMEs in Malaysia.These findings may be of help to rural-based SME owner/managers and the policy makers in finding solution for the successful implementation of ICT.